Undiagnosed Hypothyroidism in Obstructive Sleep Apnea Syndrome - Elif Torun Parmaksiz; Banu Salepçi; Gülsen Saraç; Nesrin Kiral; Ali Fidan; Sevda Cömert; Benan Çaglayan (Türk Uyku Tıbbı Dergisi, 2015)
Objective Lethargy, apathy, daytime sleepiness are common features of Obstructive sleep apnea syndrome (OSAS). These features are already seen in hypothyroidism. OSAS is more frequent in obese patients and overt hypothyroidism may substantially add to this risk. We aimed to evaluate the incidence of hypothyroidism in cases applying with OSAS symptoms who have no known clinical thyroid disease to evaluate the necessity of thyroid hormone screening in OSAS.